2009
DOI: 10.1186/1750-1164-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of diaphyseal forearm fracture-nonunions treated by autologous bone grafting and compression plating

Abstract: Background: The treatment of forearm fracture-nonunions continues to represent a therapeutic challenge, and reported outcomes are moderate at best. Limiting aspects of this particular anatomic location include the relation between restoration of shaft length with the anatomy and long-term functional outcome of adjacent joints, as well as the risk of elbow and wrist stiffness related to prolonged immobilization. The present study was designed to assess the outcome of autologous bone grafting with compression pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
(19 reference statements)
0
21
0
3
Order By: Relevance
“…[32] dos Reis et al reported excellent radiological and clinical results with application of corticocancellous grafts and plates in cases with atrophic and hypertrophic non-union. [33] In a study by Kumar et al, a union rate of 96% following LCP and autograft treatment was reported in patients with atrophic and hypertrophic nonunion of the humerus. [23] Saka et al also reported high rates of union and functional recovery using nails and autografts in cases of forearm non-union.…”
Section: Lapcin Et Al Evaluation Of Outcomes In Aseptic Non-unions Omentioning
confidence: 99%
“…[32] dos Reis et al reported excellent radiological and clinical results with application of corticocancellous grafts and plates in cases with atrophic and hypertrophic non-union. [33] In a study by Kumar et al, a union rate of 96% following LCP and autograft treatment was reported in patients with atrophic and hypertrophic nonunion of the humerus. [23] Saka et al also reported high rates of union and functional recovery using nails and autografts in cases of forearm non-union.…”
Section: Lapcin Et Al Evaluation Of Outcomes In Aseptic Non-unions Omentioning
confidence: 99%
“…The advantage of this method is that it preserves the bone length. The disadvantage is its dependence on the synthesis material, since the lower contact between the bone extremities requires the synthesis to be larger (Barbieri et al, 1997;dos Reis et al, 2009;Orzechowski et al, 2007;Reis, 2001). …”
Section: Surgical Techniques a Malunited Fracture Without A Bone Gapmentioning
confidence: 99%
“…In general, bone grafts are indicated in cases where the cause is either purely biological, or biological associated with a mechanical cause. Thus, vascularized and sometimes oligothophic malunited fractures have formal indication for bone grafting (dos Reis et al 2009;Gibson & Loadman, 1948;Haddad & Drez, 1974, Nicoll, 1956). …”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations